Nationalisms of Japan: Managing and Mystifying Identity - McVeigh, Brian J., (Rowman & Littlefield Publishers, 2004)
In this fresh and original analysis, Brian J. McVeigh confronts both the demonizers and apologists of Japan. He argues persuasively that far from being unique, Japanese nationalism becomes demystified once 'management' and 'mysticism'—the same processes and practices that operate in other national states—are taken into account. Stripping away Orientalist-inspired misconceptions, the author stresses the variety and relative intensity of nationalisms, ranging from economic, ethnic, and educational to cultural, gendered, and religious. He moves beyond state-centered ideologies to explore the linkages between official and popular nationalisms and the complex interplay of ethnocultural, ethnopolitical, and ethnoracial forms of identity. The ambiguity and everydayness of nationalism, McVeigh contends, explain its enduring power. He concludes that modern Japan is imbued with a deeply rooted legacy of 'renovationism' or 'reform nationalism' that accounts for its streamlined state structures, guarded economic nationalism, and highly scrutinized relationship with the rest of the world. Highlighting the pluralism of identity among Japanese, this book will be an invaluable corrective to recent works that glibly proclaim the emergence of 'globalization,' 'internationalization,' and 'convergence.'